Touching, unbelonging, and the absence of affect - Khanna, Ranjana (Feminist Theory, 2012)
This article argues that psychoanalytic notions of affect – including ideas of anxiety and melancholia, as well as deconstructive concepts of auto-affection – offer a feminist ethico-politics and a notion of affect as interface. Beyond the confines of the experiential and the positivist, both psychoanalysis and deconstruction provide insights into affect as a technology that understands the subject as porous. I consider works by Derek Jarman and Shirin Neshat to demonstrate the importance of the ethico-politics of affect as interface in contemporary cultural production. Both artists, in the process of considering the spectacular nature of notions of feminist and queer, use images of interface as a way of delimiting the spectacular nature of being and demonstrating the singularity of the event, the desire to fix through framing, and the parergonal nature of framing. The presence of the subject is questioned even as an auto-affection is suggestive of a spectral demand of the ethico-political. In the case of Jarman’s Blue, the denial of image as face in favour of the screen as interface is interrupted by sound and voice, which gesture toward representation as impossible but necessary. In the case of Neshat, the persistence of the photographic – the highly aesthetic self-portrait as mugshot – foregrounds face as interface, as one that questions presence through the insistence of a representational apparatus.
https://philpapers.org/rec/KHATUA
Keywords: approches et analyses; arts; arts visuels et médiatiques; discipline; photographie; psychanalyse; queer; ressource en ligne; sciences humaines; émotions